1987
DOI: 10.1007/bf00378986
|View full text |Cite
|
Sign up to set email alerts
|

Variation in herbivore density among host plants and its consequences for community structure

Abstract: The densities of four species of gall-forming sawflies were found to vary significantly among willow host plant clones. Two of the speices varied among host plants at four sites in each of three years. The other two species varied in density among host plants at most of the sites in two of the three years. Total sawfly density also varied significantly among clones. Individual species densities on willow clones were significantly positively correlated between years when all sites were combined and frequently w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…Therefore, our results do not fully support reciprocal positive (facilitation) or negative effect (competition) of one species on another gall inducing species. On the other hand, these finding are partially consistent with those of Fritz et al (1987a), who showed that sawfly species were also independently or positively (2002, 2003 and 2004) combined in each category associated among willow host plants (Fritz et al 1987b). However, competition was demonstrated in that system.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our results do not fully support reciprocal positive (facilitation) or negative effect (competition) of one species on another gall inducing species. On the other hand, these finding are partially consistent with those of Fritz et al (1987a), who showed that sawfly species were also independently or positively (2002, 2003 and 2004) combined in each category associated among willow host plants (Fritz et al 1987b). However, competition was demonstrated in that system.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Fritz (1992) demonstrated that differing genotypes of S. sericea (one of the species used in this study) varied in the structure of their insect communities. Variation in community structure among host plants has also been detected in field populations of willows (Fritz et al, 1987;Boecklen & Price, 1989), but genetic variation was not distinguished from environmental variation in those studies. More research using non-Salix populations is needed to determine the prevalence of plant genetic variation as the framework upon which arthropod communities are structured.…”
Section: Discussionmentioning
confidence: 94%
“…Seed mass is an important plant fitness component, and it is influenced by plant genotype, soil conditions, micro-and large-scale climatic trends (cf. Fritz et al 1987). Seed mass seemed to be a variable character in L. anagyroides (Tables 2, 3), although its importance in influencing seedling survival is not known.…”
Section: The Variable Nature Of Indirect Interactionsmentioning
confidence: 96%